Amenities of Literature : Consisting of Sketches and Characters of English Literature - Disraeli, Isaac, 1766-1848; Disraeli, Benjamin, Earl of Beaconsfield, 1804-1881 (Salt Lake City, UT : Project Gutenberg, 2011)
"Amenities of Literature" by Isaac Disraeli is a comprehensive literary study written in the early 19th century. The work seeks to explore the development of English literature, tracing its origins, evolution, and the influential figures behind it. Disraeli aims to provide a rich examination of how literature reflects societal changes and human thought, emphasizing the psychological aspects of literary creation. At the start of the book, Disraeli introduces his vision for a history of vernacular literature, aiming to avoid a dry narrative and instead connect literature to the social and psychological circumstances surrounding its creation. He discusses the complexity of literary origins, reflecting on the role of writers in shaping public opinion and the dynamics between authors and their societies. This foundational perspective offers insight into Disraeli's multifaceted exploration of the impact of literature on history and culture, setting the stage for a deeper investigation into specific literary figures and themes in subsequent chapters. (This is an automatically generated summary.)
The druidical institution -- Britain and the Britons -- The name of England and of the English -- The Anglo-Saxons -- Cædmon and Milton -- Beowulf; the hero-life -- The Anglo-Normans -- The page, the baron, and the minstrel -- Gothic romances -- Origin of the vernacular languages of Europe -- Origin of the English language -- Vicissitudes of the English language -- Dialects -- Mandeville; our first traveller -- Chaucer -- Gower -- Piers Ploughman -- Occleve; the scholar of Chaucer -- Lydgate; the monk of Bury -- The invention of printing -- The first English printer -- Early libraries -- Henry the Seventh -- First sources of modern history -- Arnolde's chronicle -- The first printed chronicle -- Henry the Eighth; his literary character -- Books of the people -- The difficulties experienced by a primitive author -- Skelton -- The ship of fools -- The psychological character of Sir Thomas More -- The Earl of Surrey and Sir Thomas Wyatt -- The spoliation of the monasteries -- A crisis and a reaction; Robert Crowley -- Primitive dramas -- The reformer Bishop Bale; and the Romanist John Heywood, the court jester -- Roger Ascham -- Public opinion -- Orthography and orthoepy -- The ancient metres in modern verse -- Origin of rhyme -- Rhyming dictionaries -- The arte of English poesie -- The discoverie of witchcraft -- The first Jesuits in England -- Hooker -- Sir Philip Sidney -- Spenser -- The faery queen -- Allegory -- The first tragedy and the first comedy -- The predecessors and contemporaries of Shakespeare -- Shakespeare -- The "humours" of Jonson -- Drayton -- The psychological history of Rawleigh -- The occult philosopher, Dr. Dee -- The Rosacrusian Fludd -- Bacon -- The first founder of a public library -- Early writers, their dread of the press; the transition to authors by profession -- The age of doctrines -- Pamphlets -- The Oceana of Harrington -- The author of "The grounds and reasons of monarchy" -- Commonwealth -- The true intellectual system of the universe.
Release date is 2011-06-01
E-text prepared by Marius Masi, Jonathan Ingram, and the Online Distributed Proofreading Team
Keywords: English literature -- History and criticism; Authors, English -- Biography; Great Britain -- Intellectual life